The Experiences with Qualitative Validity in a Classroom Research: Issues Pertaining to Value Claims - Okeke, Chinedu I.O. (EDUCARE, 2009)
ABSTRACT: In this paper, the writer calls into question the yet to be resolved epistemological issues about the way researchers make value claims in support of the authenticity of their research discoveries. The writer offers recognition to existing paradigmatic duality as a necessity for the third wave expressed by proponents of triangulation. Such dichotomy offers room for continuous divergence of opinions on the ways researchers perceive the empirical social world. The paper supports on-going argument that any discussion of the criteria for judging social and educational research findings must confront the issue of relativism. This position resonates through the writerâs encounter and experience with qualitative validity during a classroom study. The conclusion drawn through this encounter is that a research design is not made valid or reliable by the userâs ability to apply many verbose or exoteric terms. Instead such claim is made by the meanings, which the designs and the final report make to those for whom the study is conducted in terms of policy and practice.Â Â Â Â Â KEY WORDS: epistemology, quantitative methods, qualitative research, validity, reliability, and generalisability.About the Author: Dr. Chinedu I.O. Okeke is a Lecturer at the Department of Educational Foundations and Management UNISWA (University of Swaziland) in Africa. His contact address is Department of Educational Foundations and Management, University of Swaziland, Private Bag 4 Kwaluseni, Swaziland M201. His e-mail addresses are: ochinedu@uniswacc.uniswa.sz and okekechinedu@yahoo.comHow to cite this article? Okeke, Chinedu I.O. (2009). âThe Experiences with Qualitative Validity in a Classroom Research: Issues Pertaining to Value Claimsâ in EDUCARE: International Journal for Educational Studies, Vol.2(1) August, pp.1-16. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 17, 2009); Revised (July 17, 2009); and Published (August 17, 2009).